Crush cytology smears – A novel approach to rapid diagnosis of rhino-orbital mucormycosis in post-COVID-19 patients: A single-center study - Amruta Patil; Sagar More; Archana Patankar; Arpana Shinde (Asian Journal of Medical Sciences, 2022)
Background: With recent surge in SARS-COVID-19, cases of rhinocerebral mucormycosis are on rise. Rapid diagnosis of mucormycosis is essential as delay in the treatment is associated with dreadful outcome. Many studies have found that crush cytology smears can rapidly diagnose mucormycosis as compared to histopathology, thereby reducing the time for arriving at final diagnosis, here, we present a novel approach to the rapid diagnosis of mucormycosis by crush cytology and analyze whether it has a higher sensitivity in diagnosing cases of mucormycosis. Aims and Objectives: This study aims to analyze the efficacy of crush cytology smear in rapid diagnosis of mucormycosis. Materials and Methods: Biopsies received from all the clinically suspected cases of mucormycosis with a history or associated present COVID-19 infection. The biopsy was processed for KOH preparation, crush cytology smear and confirmation were done by histopathological examination. Special stains were done wherever necessary. Results: Out of 50 cases of clinically suspected mucormycosis, 43 confirmed on histopathology. Out of 43 confirmed cases of mucormycosis, 33 (76.74 %) were male and 10 (23.25%) were female with male: female ratio of 3.3:1. The mean age of the studied cases was found to be 52.32±12.59 years. The most common presenting complaint was fever (79.07%), followed by headache/retro-orbital pain (62.79%), rhinorrhea (58.14%), and facial swelling (53.49%). Out of 43 patients, 41 recovered from COVID-19 disease with mean duration of 12 days. Hospital stays of patients with for COVID-19 varied from 7 days to maximum of 35 days. Out of 43 cases of mucormycosis, 24 cases were diagnosed with KOH mount with sensitivity of 55.81% and 39 cases with crush cytology smears with sensitivity of 90.69%. Conclusion: The diagnosis of mucormycosis is done with the gold standard methods such as histopathological examination and culture studies but the present study emphasizes on use of crush cytological smears prepared from sinonasal biopsies in suspected cases of mucormycosis in rapid and accurate diagnosis of mucormycosis.